Blood coagulation abnormalities in multibacillary leprosy patients. - Débora Santos da Silva; Lisandra Antonia Castro Teixeira; Daniela Gois Beghini; André Teixeira da Silva Ferreira; Márcia de Berredo Moreira Pinho; Patricia Sammarco Rosa; Marli Rambaldi Ribeiro; Monica Di Calafiori Freire; Mariana Andrea Hacker; José Augusto da Costa Nery; Maria Cristina Vidal Pessolani; Ana Maria Freire Tovar; et al. (Public Library of Science (PLoS), 2018)
Leprosy is a chronic dermato-neurological disease caused by Mycobacterium leprae infection. In 2016, more than 200,000 new cases of leprosy were detected around the world, representing the most frequent cause of infectious irreversible deformities and disabilities.In the present work, we demonstrate a consistent procoagulant profile on 40 reactional and non-reactional multibacillary leprosy patients. A retrospective analysis in search of signs of coagulation abnormalities among 638 leprosy patients identified 35 leprosy patients (5.48%) which displayed a characteristic lipid-like clot formed between blood clot and serum during serum harvesting, herein named 'leprosum clot'. Most of these patients (n = 16, 45.7%) belonged to the lepromatous leprosy pole of the disease. In addition, formation of the leprosum clot was directly correlated with increased plasma levels of soluble tissue factor and von Willebrand factor. High performance thin layer chromatography demonstrated a high content of neutral lipids in the leprosum clot, and proteomic analysis demonstrated that the leprosum clot presented in these patients is highly enriched in fibrin. Remarkably, differential 2D-proteomics analysis between leprosum clots and control clots identified two proteins present only in leprosy patients clots: complement component 3 and 4 and inter-alpha-trypsin inhibitor family heavy chain-related protein (IHRP). In agreement with those observations we demonstrated that M. leprae induces hepatocytes release of IHRP in vitro.We demonstrated that leprosy MB patients develop a procoagulant status due to high levels of plasmatic fibrinogen, anti-cardiolipin antibodies, von Willebrand factor and soluble tissue factor. We propose that some of these components, fibrinogen for example, presents potential as predictive biomarkers of leprosy reactions, generating tools for earlier diagnosis and treatment of these events.